PENGEMBANGAN MEDIA PEMBELAJARAN PEMBANGKIT LISTRIK TENAGA UAP UNTUK MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DI SMA NEGERI 2 SINGARAJA - kadek dwi saputra; I Putu Suka Arsa; Nyoman Santiyadnya (Jurnal Pendidikan Teknik Elektro Undiksha, 2022)
This study aims to create a Steam Power Plant Learning Media at SMA Negeri 2 Singaraja. Knowing the feasibility of the Steam Power Plant Learning Media, and knowing the responses of students to this learning media. This research is an R&D (Research and Development) research. This study uses the statistical analysis of percentages used in processing the data of content experts, media experts, and field trials. This study used a questionnaire as an instrument for collecting data from content experts, media experts, and students. The results obtained: the results of the media expert test got a percentage of 96.42% with very decent qualifications, and the content expert validation test got a percentage of 95.45% with very decent qualifications. The range of scores for 6 small group test respondents is included in the very high qualification, and the score range for 37 large group test respondents is included in the very high classification. Steam Power Plant Learning Media for Craft and Entrepreneurship Subjects is appropriate to be used in the learning process.